Inverse Agonist and Pharmacochaperone Properties of MK-0524 on the Prostanoid DP1 Receptor - Labrecque, Pascale; Roy, Sébastien J.; Fréchette, Louis; Iorio-Morin, Christian; Gallant, Maxime A.; Parent, Jean-Luc (PLOS ONE, 2013)
Prostaglandin D2 (PGD2) acts through two G protein-coupled receptors (GPCRs), the prostanoid DP receptor and CRTH2 also known as DP1 and DP2, respectively. Several previously characterized GPCR antagonists are now classified as inverse agonists and a number of GPCR ligands are known to display pharmacochaperone activity towards a given receptor. Here, we demonstrate that a DP1 specific antagonist, MK-0524 (also known as laropiprant), decreased basal levels of intracellular cAMP produced by DP1, a Gαs-coupled receptor, in HEK293 cells. This reduction in cAMP levels was not altered by pertussis toxin treatment, indicating that MK-0524 did not induce coupling of DP1 to Gαi/o proteins and that this ligand is a DP1 inverse agonist. Basal ERK1/2 activation by DP1 was not modulated by MK-0524. Interestingly, treatment of HEK293 cells expressing Flag-tagged DP1 with MK-0524 promoted DP1 cell surface expression time-dependently to reach a maximum increase of 50% compared to control after 24 h. In contrast, PGD2 induced the internalization of 75% of cell surface DP1 after the same time of stimulation. The increase in DP1 cell surface targeting by MK-0524 was inhibited by Brefeldin A, an inhibitor of transport from the endoplasmic reticulum-Golgi to the plasma membrane. Confocal microscopy confirmed that a large population of DP1 remained trapped intracellularly and co-localized with calnexin, an endoplasmic reticulum marker. Redistribution of DP1 from intracellular compartments to the plasma membrane was observed following treatment with MK-0524 for 24 h. Furthermore, MK-0524 promoted the interaction between DP1 and the ANKRD13C protein, which we showed previously to display chaperone-like effects towards the receptor. We thus report that MK-0524 is an inverse agonist and a pharmacochaperone of DP1. Our findings may have important implications during therapeutic treatments with MK-0524 and for the development of new molecules targeting DP1.